2018
DOI: 10.1111/1475-6773.12997
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nursing Satisfaction and Turnover Cognitions on Patient Attitudes and Outcomes: A Three‐Level Multisource Study

Abstract: These findings provide evidence of the importance of nurse attitudes in improving perceived and actual performance across facilities and health care systems; in addition to practical steps, managers can take to improve satisfaction and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 85 publications
4
33
0
1
Order By: Relevance
“…This study indicates that nurses perceived that their positive job attitudes in uenced positive organizational outcomes. This was aligned with past research about nurse attitudes in outpatient settings indicating that higher levels of nurses' job satisfaction was associated with lower levels of nurse turnover (5-7) and patient falls (40). These ndings have implications for health policy as they indicate a need to invest in job and personal factors that promote positive job attitudes, so nurses can do their jobs well.…”
Section: How Nurses' Job Attitudes Affect Their Ability To Do Their Jobssupporting
confidence: 84%
“…This study indicates that nurses perceived that their positive job attitudes in uenced positive organizational outcomes. This was aligned with past research about nurse attitudes in outpatient settings indicating that higher levels of nurses' job satisfaction was associated with lower levels of nurse turnover (5-7) and patient falls (40). These ndings have implications for health policy as they indicate a need to invest in job and personal factors that promote positive job attitudes, so nurses can do their jobs well.…”
Section: How Nurses' Job Attitudes Affect Their Ability To Do Their Jobssupporting
confidence: 84%
“…Extant literature on employee satisfaction has shown that while its determinants may vary among different jobs, it has a crucial influence on worker's performance (Jalagat, 2016; Torlak & Kuzey, 2019). In the case of healthcare, nurse satisfaction is a consistent predictor of nursing performance and patient satisfaction (Ahmad et al., 2017; Perry et al., 2018; Putra et al., 2017). This link is also observed when using longitudinal data (Shazadi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A successful nurse drifted injection clinic relies on satis ed nurses, as increased well-being rises the quality of the work [7] and leads to satis ed patients [8][9][10]. Job satisfaction among nurses is a recurring theme in the literature [11][12][13], but studies of nurses' satisfaction concerning task shifting and training are scarce.…”
Section: Introductionmentioning
confidence: 99%